The Effect Of Vocational Pedagogy Learning On Students' Professional Readiness For Teaching In The School Internship Program (PLK) In The Field Of Mechanical Engineering (Jurnal Vokasi Mekanika, 2025)
The Vocational Pedagogy course is an important factor in supporting students' teaching readiness. Observation shows that PLK students have a gap in teaching readiness even though they have taken Vocational Pedagogy courses. This study describes the teaching readiness of students in the Mechanical Engineering Department at Padang State University and analyzes the effect of the course on teaching readiness. The study employed a causal quantitative approach, surveying 92 students from the 2020 and 2021 cohorts, selected via Proportionate Stratified Random Sampling. Data were collected via a questionnaire and analyzed using descriptive analysis and simple linear regression. The results showed that students' mastery of the Vocational Pedagogy course was high, with an average score of 4.5. Students' teaching readiness was also in the "ready" category, with an average score of 4.5. Hypothesis testing results show that vocational pedagogy courses positively and significantly impact student teaching readiness. The coefficient of determination (R-square) is 0.545, meaning 54.5% of teaching readiness variables are influenced by vocational pedagogy courses, while other factors influence the rest. This study concludes that Vocational Pedagogy courses significantly and positively impact teaching readiness among students in the Department of Mechanical Engineering at FT-UNP. Micro teaching is a crucial factor in improving teaching readiness in this course.